Living well in a down economy (--For dummies., 2023)
"Living Well in a Down Economy for Dummies offers dozens of practical tips for navigating a recession with confidence and keeping some cash in your pocket. Discover ideas for increasing your income, getting your finances together, cutting costs, and managing debt." -- Back cover.